Two girls, fat and thin / Mary Gaitskill. - Gaitskill, Mary, 1954- (Penguin modern classics., 2021)
Dorothy Never, fat, lives alone in New York, eats and works the night shift as a proofreader. Justine Shade, thin, is a freelance journalist who sleeps with unsuitable men. Both are isolated. Both are damaged by their pasts. When Justine interviews Dorothy about her involvement with an infamous and charismatic philosophical guru, the two women are drawn together with an intense magnetism that throws their lives off balance.